Visual Web Developer 2005 Express Edition for Dummies - Simpson, Alan (Wiley Publishing, 2011)
Visual Web Developer Express Edition is a low-cost, entry-level version centered around pre-built projects that new developers can easily deploy and customize for their own sites Explains how to harness "drag-and-drop" tools that build on the popularity of ASP.NET, offering Web designers an easy introduction to the new Microsoft Visual Studio 2005 Framework Shows novice Web developers step by step how to create powerful ASP.NET Web applications Explains how to access databases through Data Source controls, design site navigation, build interactivity, and much more